Structure and scale of the mechanics of mammalian dental enamel viewed from an evolutionary perspective. Issue 1 (14th December 2015) - Lucas, Peter W.; Philip, Swapna M.; Al‐Qeoud, Dareen; Al‐Draihim, Nuha; Saji, Sreeja; van Casteren, Adam
SUMMARY: Mammalian enamel, the contact dental tissue, is something of an enigma. It is almost entirely made of hydroxyapatite, yet exhibits very different mechanical behavior to a homogeneous block of the same mineral. Recent approaches suggest that its hierarchical composite form, similar to other biological hard tissues, leads to a mechanical performance that depends very much on the scale of measurement. The stiffness of the material is predicted to be highest at the nanoscale, being sacrificed to produce a high toughness at the largest scale, that is, at the level of the tooth crown itself. Yet because virtually all this research has been conducted only on human (or sometimes "bovine") enamel, there has been little regard for structural variation of the tissue considered as evolutionary adaptation to diet. What is mammalian enamel optimized for? We suggest that there are competing selective pressures. We suggest that the structural characteristics that optimize enamel to resist large‐scale fractures, such as crown failures, are very different to those that resist wear (small‐scale fracture). While enamel is always designed for damage tolerance, this may be suboptimal in the enamel of some species, including modern humans (which have been the target of most investigations), in order to counteract wear. The experimental part of this study introduces novel techniques that help to assess resistance at the nanoscale.